Technical efficiency of improved and local variety seed maize farms in Ghana: A meta-frontier analysis - Theophilus Tweneboah Kodua; Edward E. Onumah; Akwasi Mensah-Bonsu (Cogent Economics & Finance, 2022)
The meta-frontier model technique is employed to compare the technical efficiency levels of improved and local maize seed variety farms in Ghana using a cross-sectional data from 214 farmers. The study shows that inefficiencies in maize production relate to exogenous variables considered even though some of the variables are not statistically significant. All input variables considered contribute positively to maize output in both improved and local seed varieties as well as in the pooled data. Maize farms generally exhibit increasing returns to scale (IRS) in the study area. The mean technical efficiency relative to the meta-frontier is estimated to be 72%, 44% and 50% for the improved, local maize seed variety farms and the pooled data respectively. Based on the estimated TGR of 90% and 72% for the improved and local seed variety maize farms, respectively, the study concludes that maize farmers who cultivated improved maize seed varieties are more technically efficient compared to their counterparts who do otherwise. It is recommended that stakeholder efforts should focus on labour source, education, extension contacts, ready market availability and credit that contribute positively to farmers' efficiency to further increase maize output in Ghana. Furthermore, farmers should be encouraged and educated more on the benefits of newly developed varieties of maize so that they will be convinced enough to adopt in order to increase their output in the near future.
Keywords: 330; technology gap ratio; returns to scale; stochastic frontier; maize production; Ghana